Using a value chain framework for food safety assessment of edible offals in Nairobi, Kenya - Sirma, Anima; Muthuma, Evans; Kariuki, John; Maina, Agnes; Thaiya, Joyce; Njagi, Obadiah (Frontiers in Sustainable Food Systems, 2023)
Edible offals comprise those parts of the animal considered fit for human consumption apart from the skeletal muscle, fat and attached skin. Edible offals form an important source of affordable animal protein and a delicacy for the larger Kenyan market. The offals are mainly traded in the informal markets which supplies at least 80% of the domestic market and where hygiene levels are low. The Meat Control Act Chapter 356, Laws of Kenya (Revised 2012) requires that offals be obtained from an officially declared food animal that has been slaughtered in a licensed slaughterhouse and declared fit for human consumption. According to the Meat Control Act, slaughterhouses in Kenya are classified as either export or local. The latter is subdivided into categories A, B, and C depending on their daily capacity, land size and the area they are authorized to supply meat and meat products. Each export slaughterhouse, category A and B slaughterhouses require a minimum of three meat inspectors to carry out inspection of carcasses and offals. The Directorate of Veterinary Services is the main regulator in Kenya on matters concerning safety of meat at the slaughterhouses. The Director of Veterinary Services appoints meat inspectors and veterinary officers who are responsible for ascertaining the safety of meat and meat products from the slaughterhouses. The meat inspectors also verify that slaughter facilities, staff, processes and equipment conform to food safety requirements. Offals, like carcass meat, should be handled under utmost hygiene conditions to minimize contamination or excessive growth of microorganisms. The current practices in slaughterhouses is that each set of edible offals is packaged separately in either polythene bags, plastic containers, meat transport containers or carriers and dispatched to the market. In some instances, stomachs and intestines are packaged for dispatch together with the lungs and hearts for transportation to distances over 50 km in either refrigerated or non-refrigerated containers or carriers. Some of these practices could compromise the safety of the offals. In this paper, we review the challenges faced in maintaining safety of edible offals especially at the slaughterhouses, distributors and retailers level from regulators' point of view.